Predicting muscularity-related behavior, emotions, and cognitions in men: The role of psychological need thwarting, drive for muscularity, and mesomorphic internalization. (September 2016) - Edwards, Christian; Tod, David; Molnar, Gyozo; Markland, David
Highlights: Examined relationships need thwarting has with appearance-related variables in men. Need thwarting predicted weightlifting. Need thwarting/drive for muscularity interaction predicted muscle dissatisfaction. Need thwarting/internalization interaction predicted muscle dissatisfaction. Men's muscularity-focused issues may be tied to basic human needs. Abstract: We examine the relationships that internalization, need thwarting (NT), and drive for muscularity (DFM), along with their interactions, had with weightlifting, muscle dissatisfaction (MD), and muscle-related-worry (MRW). A sample of 552 men ( M Age = 20.5 years, SD = 3.1) completed the Psychological Need Thwarting Scale, the Internalization subscale of the male version of the Sociocultural Attitudes Towards Appearance Questionnaire, the Drive for Muscularity Scale-Attitudes subscale, the Male Body Attitudes Scale-Muscularity subscale, the Body Change Inventory-Worry subscale, and an inventory assessing weightlifting behavior. DFM significantly predicted weightlifting, MRW, and MD. Internalization significantly predicted weightlifting and MRW. NT significantly predicted weightlifting and MD, and its relationship with MRW approached significance. The interaction terms did not predict weightlifting or MRW. The NT/DFM and NT/Internalization interaction terms predicted MD. These results highlight the role of NT in predicting appearance variables in men.